Scoping Operational Readiness and Investigating Its Financial Impact in Capital Projects: A Study of the South African Platinum Mining Sector - Du Toit, Lena Louise (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.